PENERAPAN MODEL PEMBELAJARAAN KOOPERATIF MAKE A MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA - Yanda Marlina (Jurnal Edukasi dan Penelitian Matematika, 2018)
One of the important things in learning mathematics is understanding of mathematical concepts. The fact, understanding of mathematical concepts studets in class VIII of SMPN 3 Padang still low. The observation concluded that the causes is when teacher explain the subject, most students interact with friends. In addition, students are less enthusiatics about doing the exercises. One of the efforts to improve it by applying the learning model that involves the participation of students in learning and doing the exercises is cooperative learning model Make a Match. The type of research is quasi experiment with static group design. The technique is simple random sampling. Analysis of data used is t-test. Based on the analysis data obteined the average of the experimental class are 66.74 and the control class is 54.68. The result concluded that understanding mathematical concept of students learning by cooperatif learning model Make a Match is better than understanding mathematical concept students learning by conventional learning.Keywords – understanding of mathematical concepts, cooperative learning, make a match type, conventional learning